Decomposing variation in male reproductive success: age‐specific variances and covariances through extra‐pair and within‐pair reproduction. (7th March 2013) - Lebigre, Christophe; Arcese, Peter; Reid, Jane M.; Jones, James
Summary Age‐specific variances and covariances in reproductive success shape the total variance in lifetime reproductive success (LRS), age‐specific opportunities for selection, and population demographic variance and effective size. Age‐specific (co)variances in reproductive success achieved through different reproductive routes must therefore be quantified to predict population, phenotypic and evolutionary dynamics in age‐structured populations. While numerous studies have quantified age‐specific variation in mean reproductive success, age‐specific variances and covariances in reproductive success, and the contributions of different reproductive routes to these (co)variances, have not been comprehensively quantified in natural populations. We applied 'additive' and 'independent' methods of variance decomposition to complete data describing apparent (social) and realised (genetic) age‐specific reproductive success across 11 cohorts of socially monogamous but genetically polygynandrous song sparrows (Melospiza melodia). We thereby quantified age‐specific (co)variances in male within‐pair and extra‐pair reproductive success (WPRS and EPRS) and the contributions of these (co)variances to the total variances in age‐specific reproductive success and LRS. 'Additive' decomposition showed that within‐age and among‐age (co)variances in WPRS across males aged 2–4 years contributed most to the total variance in LRS. Age‐specific (co)variances in EPRS contributed relatively little. However, extra‐pair reproduction altered age‐specific variances in reproductive success relative to the social mating system, and hence altered the relative contributions of age‐specific reproductive success to the total variance in LRS. 'Independent' decomposition showed that the (co)variances in age‐specific WPRS, EPRS and total reproductive success, and the resulting opportunities for selection, varied substantially across males that survived to each age. Furthermore, extra‐pair reproduction increased the variance in age‐specific reproductive success relative to the social mating system to a degree that increased across successive age classes. This comprehensive decomposition of the total variances in age‐specific reproductive success and LRS into age‐specific (co)variances attributable to two reproductive routes showed that within‐age and among‐age covariances contributed substantially to the total variance and that extra‐pair reproduction can alter the (co)variance structure of age‐specific reproductive success. Such covariances and impacts should consequently be integrated into theoretical assessments of demographic and evolutionary processes in age‐structured populations.